Environmentally harmful subsidies challenges for reform. (OECD, 2005)
Subsidies are pervasive throughout OECD countries and much of this support is potentially harmful environmentally. This report presents sectoral analyses on agriculture, fisheries, water, energy and transport, proposing a checklist approach to identifying and assessing environmentally harmful subsidies. It also identifies the key tensions and conflicts that are likely to influence subsidy policy making. The book concludes with a discussion of politically feasible subsidy reform strategies.--Publisher's description.